Psychometric properties of the Emotional Intelligence scale TMMS-24 in adults of Metropolitan Lima, 2020 - Pérez Zarate, José Fernando (2020)
The present study aimed to analyze the psychometric properties of the TMMS-24 Emotional Intelligence scale in an adult population of Metropolitan Lima 2020. The research was instrumental in design. 430 participants were surveyed, of which filters were made, obtaining 211 good data. The test used was the TMMS-24 scale by Mayer and Salovey (1995), adapted to the Spanish language by Fernández-Berrocal, Extremera and Ramos (2004). The scale has 24 items where item 5 presents a low index of homogeneity, commonality and discrimination. In the Confirmatory Factor Analysis, indicators were used to analyze the fit of the model, CFI = .838, TLI = 846, RMSEA = .070 and SRMR = .085. When analyzing the relationship with other variables, a positive correlation was found with the WHO-FIVE (> .30) and a discriminant correlation with the DASS-21 (<.20). On the other hand, in the reliability analysis I show a greater similarity between alpha (.87) and omega (.85) in the Regulation dimension. Finally, in the equity analysis it was evidenced that the scale is invariant (∆CFI <.01; ∆RMSEA <.01) between men and women.